Highly Sensitive Colorimetric Biosensor for Staphylococcal Enterotoxin B by a Label-Free Aptamer and Gold Nanoparticles - Mondal, Bhairab; Ramlal, Shylaja; Lavu, Padma S.; N, Bhavanashri; Kingston, Joseph (Frontiers in Microbiology, 2018)
Abstract A simple, sensitive and selective colorimetric biosensor for the detection of Staphylococcal enterotoxin B (SEB) was developed using SEB-binding aptamer (SEB2) as recognition element and unmodified gold nanoparticles (AuNPs) as colorimetric probes. The assay is based on color change from red to purple due to conformational change of aptamer in the presence of SEB, and the phenomenon of salt-induced AuNPs aggregation which could be monitored by naked eye or UV–vis spectrometer. Results showed that the AuNPs can effectively differentiate the SEB induced conformational change of the aptamer in the presence of a given high salt concentration. A linear response in the range of 50 µg/mL to 0.5 ng/mL of SEB concentration was obtained. The assay was highly specific to SEB as compared to other related toxins. The limit of detection (LOD) of SEB achieved within few minutes was 50 ng/mL visually and spectrometric method improved it to 0.5 ng/mL. Robustness of the assay was tested in artificially spiked milk samples and cross-checked using in house developed sandwich ELISA (IgY as capturing and SEB specific monoclonal as revealing antibody) and PCR. This colorimetric assay could be a suitable alternative over existing methods during biological emergencies due to its simplicity, sensitive and cost effectiveness.